2011
DOI: 10.1016/j.patcog.2010.09.009
|View full text |Cite
|
Sign up to set email alerts
|

A Riemannian scalar measure for diffusion tensor images

Abstract: We study a well-known scalar quantity in Riemannian geometry, the Ricci scalar, in the context of Diffusion Tensor Imaging (DTI), which is an emerging non-invasive medical imaging modality. We derive a physical interpretation for the Ricci scalar and explore experimentally its significance in DTI. We also extend the definition of the Ricci scalar to the case of High Angular Resolution Diffusion Imaging (HARDI) using Finsler geometry. We mention that Ricci scalar is not only suitable for tensor valued image ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

6
3

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…The prevalence and geometry of sheet structures in the brain can potentially also be a novel feature to characterize brain structure, complementing the wide range of existing microstructural and geometrical measures (e.g. (Assaf et al, 2008; Astola et al, 2011; Dell’acqua et al, 2013; Fieremans et al, 2011; Leemans et al, 2006; Raffelt et al, 2012; Savadjiev et al, 2012; Tax et al, 2012; Zhang et al, 2012)).…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence and geometry of sheet structures in the brain can potentially also be a novel feature to characterize brain structure, complementing the wide range of existing microstructural and geometrical measures (e.g. (Assaf et al, 2008; Astola et al, 2011; Dell’acqua et al, 2013; Fieremans et al, 2011; Leemans et al, 2006; Raffelt et al, 2012; Savadjiev et al, 2012; Tax et al, 2012; Zhang et al, 2012)).…”
Section: Introductionmentioning
confidence: 99%
“…Another advantage with respect to other types of tracking algorithms is that geodesic tractography tends to be more robust to noise. Finally, it has the conceptual advantage that Riemannian geometry is a well understood and powerful theoretical machinery, facilitating mathematical modelling and algorithmics [2][3][4]6,12,[15][16][17][24][25][26]30,31,33,35].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Riemann scalar measure has been applied to diffusion tensor imaging [28]. An early work by Huttenlocher et al found that Hausdorff distance is especially useful in dealing with images with small perturbation [29].…”
Section: Y Feng Et Al / a Modified Fcm For Mr Images Segmentationmentioning
confidence: 99%